LEDs for photons, physiology and food. (22nd November 2018) - Pattison, P.; Tsao, J.; Brainard, G.; Bugbee, B.
Abstract Lighting based on light-emitting diodes (LEDs) not only is more energy efficient than traditional lighting, but also enables improved performance and control. The colour, intensity and distribution of light can now be controlled with unprecedented precision, enabling light to be used both as a signal for specific physiological responses in humans and plants, and as an efficient fuel for fresh food production. Here we show how a broad and improved understanding of the physiological responses to light will facilitate greater energy savings and provide health and productivity benefits that have not previously been associated with lighting. This Perspective discusses developments in LED-based solid-state lighting for physiological and agricultural applications, and the anticipated benefits in terms of health and productivity.